Effect of Temperature on the Biodegradation of Glyphosate by Soil Bacteria - Aziz, Muhammad Baihaqi Che Ab; Ariffin, Fazilah (Journal of Environmental Bioremediation and Toxicology, 2024)
Glyphosate, a broad-spectrum systemic herbicide, is widely used in agriculture to control weeds. Its extensive use has raised concerns about its environmental impact and persistence in ecosystems. Understanding the biodegradation of glyphosate is crucial for evaluating its long-term effects and developing effective remediation strategies. Biodegradation is the process by which microorganisms break down substances and plays a vital role in mitigating the accumulation of harmful compounds in the environment. Therefore, this study investigates the effect of temperature on glyphosate degradation by soil bacteria, which is crucial for understanding its breakdown in soil ecosystems. Soil bacteria have shown potential in degrading glyphosate, but the impact of temperature remains understudied. The research aims to study the effect of temperature conditions on glyphosate degradation by soil bacteria. Soil samples were collected from Mardi Bachok, Kelantan, and their coordinates, pH, and temperature were recorded. Soil samples were incubated in Mineral Salts Medium (MSM) containing 100 mg/L glyphosate at 28°C and 37°C for seven days, with optical density measured every 24 hours. Both temperature treatments showed microbial communities capable of thriving in glyphosate-supplemented MSM, utilizing it as a sole carbon and phosphate source. Statistical analysis revealed no significant difference in microbial growth between the two temperatures. These results suggest that soil bacteria are capable of thriving in a range of temperature conditions while effectively degrading glyphosate. Understanding these dynamics is essential for developing effective bioremediation strategies and predicting the environmental fate of glyphosate in various climatic conditions. Future research should explore additional environmental factors and microbial interactions to further elucidate the complexities of glyphosate biodegradation in soil ecosystems.